Risk stratification in patients with upper gastrointestinal submucosal tumors undergoing submucosal tunnel endoscopic resection - Lv, Yong; Li, Shaohua; Lv, Xiuhe; Liu, Qing; Zheng, Yu; Su, Yang; Yang, Changbin; Pan, Yanglin; Yao, Liping; Xie, Huahong (Frontiers in Medicine, 2022)
Background A substantial heterogeneity exists in patients with upper gastrointestinal submucosal tumors (SMTs). This study aimed to identify predictors of long procedure time (≥60 min), occurrence of procedure-related complications, and long hospital stay (≥6 days) in patients with SMTs undergoing submucosal tunnel endoscopic resection (STER) and stratify risk based on the predictors. Methods Sixty-six consecutive patients with upper gastrointestinal SMTs undergoing STER between January 2013 and December 2018 were retrospectively included. Binary logistic regression models were developed to identify predictors of outcomes. Receiver operating characteristic (ROC) curves were constructed to evaluate the discrimination of tumor size. Results Complete resection and en bloc resection of tumor were achieved in 66 (100%) and 64 patients (97%), respectively. Twenty-seven patients (41%) had a long procedure time, 10 (15%) developed STER-related complications, and 17 (26%) had a long hospital stay. On multivariable analysis, tumor size was an independent predictor of long procedure time (OR 1.37, 95% CI 1.13–1.67; p = 0.001), occurrence of complications (OR 1.06, 95% CI 1.01–1.10; p = 0.012), and long hospital stay (OR 1.05, 95% CI 1.01–1.09; p = 0.035). ROC curves identified a tumor of size 25 mm as the best cutoff; those who had a tumor above this value had a 76-fold risk of long procedure time, 8.56-fold risk of occurrence of complications, and 6.35-fold risk of long hospital stay. Conclusion Patients with a tumor size ≥25 mm had longer procedure time, higher risk of STER-related complications, and longer hospital stay; therefore, they should be classified as a high-risk group.